Relationship between socioeconomic status dimensions and academic anxiety of college students - Apolonio, Marypaul Louise; Malcampo, Marie Chiela; Rungduin, Teresita (Institut Agama Islam Negeri Langsa, 2025)
This quantitative correlational study examined the relationship between various dimensions of socioeconomic status (SES) and academic anxiety among 330 Filipino college students in Metro Manila, Phillipines. Data were collected through online surveys utilizing two adapted instruments: a 10-item Socioeconomic Status Questionnaire and an 11-item Academic Anxiety Scale. Pearson correlation and multiple regression analyses were conducted to assess the associations and predictive strength of SES indicators—such as parental education and occupation, family income, family size, gender, and age—on academic anxiety. Results revealed that higher paternal education and office-type paternal occupations were significantly associated with increased academic anxiety, while lower paternal education and manual labor occupations were associated with reduced anxiety. Family income exceeding ?20,001 was positively correlated with anxiety, possibly due to increased academic expectations. Regression analysis showed that paternal education, paternal occupation, family size, and student age collectively explained 19.9% of the variance in academic anxiety. These findings highlight the nuanced effects of SES, particularly paternal factors, on students' psychological stress. The study underscores the importance of culturally responsive support strategies such as parental education workshops, financial literacy training, and targeted anxiety interventions for students. Future research should consider longitudinal and qualitative methods to explore the underlying cultural mechanisms and long-term outcomes.